2008
DOI: 10.1117/1.2931078
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of breast cancer using fluorescence and diffuse reflectance spectroscopy: a Monte-Carlo-model-based approach

Abstract: We explore the use of Monte-Carlo-model-based approaches for the analysis of fluorescence and diffuse reflectance spectra measured ex vivo from breast tissues. These models are used to extract the absorption, scattering, and fluorescence properties of malignant and nonmalignant tissues and to diagnose breast cancer based on these intrinsic tissue properties. Absorption and scattering properties, including β-carotene concentration, total hemoglobin concentration, hemoglobin saturation, and the mean reduced scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
99
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(114 citation statements)
references
References 38 publications
14
99
0
1
Order By: Relevance
“…IFS detects endogenous fluorophores, including enzymes, metabolic cofactors, amino acids, porphyrins, and structural proteins. IFS has been used to detect bronchopulmonary cancer (19), epithelial precancerous tissue (20), laryngeal cancer (21), and breast cancer (22). DRS provides information from tissue absorbers, including oxygenated and deoxygenated hemoglobin, lipids, water, cytochromes, and melanin (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…IFS detects endogenous fluorophores, including enzymes, metabolic cofactors, amino acids, porphyrins, and structural proteins. IFS has been used to detect bronchopulmonary cancer (19), epithelial precancerous tissue (20), laryngeal cancer (21), and breast cancer (22). DRS provides information from tissue absorbers, including oxygenated and deoxygenated hemoglobin, lipids, water, cytochromes, and melanin (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Over the last decade, new tools have been developed to classify breast tissue and assess breast tissue margins based on optical spectroscopy techniques. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Bigio et al performed in vivo elastic scattering spectroscopy measurements between 350 and 750 nm to discriminate between 13 malignant and 59 nonmalignant breast tissue samples by applying artificial neural network (ANN) and hierarchical cluster analysis on the spectra yielding sensitivity-specificity of 69%-85% and 67%-79%, respectively. 9 This study also showed that the spectral features between 400 and 500 nm in adipose tissue are mainly dominated by β-carotene light absorption, however optical properties were not derived from the measured spectra.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Diffuse reflectance spectra have been used to estimate the optical properties of tissues, 3 which can be correlated with several important biophysical and biochemical parameters, such as hemoglobin information, 2 tissue oxygenation, 2 and average nuclei size 4 in tissues for disease diagnoses. Nonetheless, one significant disadvantage of traditional diffuse reflectance spectroscopy is slow data acquisition when diffuse reflectance spectra at multiple locations are required due to the employment of fiber-optic probes, which can only perform optical measurements point by point.…”
mentioning
confidence: 99%